Study on the Morphology and Mechanical Properties of Cynodon dactylon in the Riparian Zone Slopes of a Large Reservoir - Pengyu Zhang; Pengcheng Wang; Siyuan Jin (Applied Sciences, 2024)
The stability of riverbank slopes is crucial in watershed ecology. The morphology and tensile strength properties of plant roots play a significant role in slope stability, which is of great importance for the ecological stability of riverbanks. The Jinsha and Yalong River basins are the largest hydropower bases in China and are in the ecologically fragile areas of the dry and hot river valleys, yet fewer studies are available on these basins. Further studies on the growth morphology and root mechanical properties of plant roots in the riparian zone at different elevations have not been reported. Therefore, we selected the dominant species of Cynodon dactylon root as the research subject, analyzed the root morphology, and conducted indoor single-root tensile tests to study its root structure and mechanical properties at various elevations. The results showed that the root morphology of Cynodon dactylon was positively correlated with elevation. Compared to low elevations (L and M), the root length increased by 57.3% and 21.47%, the root diameter increased by 24.85% and 13.92%, the root surface area increased by 93.5% and 67.37%, and the total root volume increased by 119.91% and 107.36%. As the elevation gradient increased, the flooding time decreased, leading to more developed plant roots for Cynodon dactylon. The Young’s modulus ranged from 148.43 to 454.18 MPa for Ertan Cynodon dactylon roots and 131.31 to 355.53 MPa for Guanyingyan Cynodon dactylon roots. The maximum tensile strength, ultimate tensile strength, ultimate elongation, and Young’s modulus of the plant root of the Cynodon dactylon showed a power function relationship with the diameter. The maximum tensile strength increased as the diameter increased, while the remaining properties decreased following a power function relationship. The maximum tensile strength, ultimate tensile strength, and Young’s modulus of Cynodon dactylon were positively correlated with elevation, while the ultimate elongation was negatively correlated with elevation. The results elucidate the influence of elevation on the root morphology and mechanical properties of dominant riparian species. This provides a theoretical basis for managing and protecting riparian slopes in ecologically fragile areas.